2017
DOI: 10.1039/c6ra28865k
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of donor-to-acceptor feed ratios with the aim of obtaining black-to-transmissive switching polymers based on isoindigo as the electron-deficient moiety

Abstract: The polymers based on isoindigo, thiophene and ProDOT were synthesized and characterized. Black to transmissive polymers were obtained by controlling the feed ratios of the units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Compared with inorganic electrochromic compounds, such as WO 3 and IrO 2 , soluble polymeric electrochromic materials have some merits, including the ease of the fabrication of large films, bright colors, large optical contrast ratios, and fast response speeds [ 12 ]. Furthermore, the bandgaps of the D-A-type polymers can be easily modulated by structural modification through the selection of proper donor or acceptor units for stronger or weaker ones, or by changing the donor-to-acceptor ratios within the polymer backbone [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with inorganic electrochromic compounds, such as WO 3 and IrO 2 , soluble polymeric electrochromic materials have some merits, including the ease of the fabrication of large films, bright colors, large optical contrast ratios, and fast response speeds [ 12 ]. Furthermore, the bandgaps of the D-A-type polymers can be easily modulated by structural modification through the selection of proper donor or acceptor units for stronger or weaker ones, or by changing the donor-to-acceptor ratios within the polymer backbone [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different molecular ratios of the monomers in the different polymers i.e TP-1, TP-2 & TP-3, the relative strengths of the specific absorption peaks varied, although the absorption profiles and peak locations of the polymers were nearly the same as each other. [23] Six vibrational bands were appeared for both polymers (TP-1 and TP-2) from 2800-3000 cm À 1 i.e CÀ H stretching with medium appearance (aromatic, alkane 2) corresponds to C=C bending signifies the presence of pyrene moiety in thepolymers. [24] All the synthesized terpolymers are highly soluble in chloroform, chlorobenzene, THF at room temperate, which lead to molecular weights with a number-average molecular weight (M n ) of 4200 g/mol, 4800 g/mol and 2500 g/mol, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 96%
“…It was observed that the T% was greatly dependent on the switching time and the two polymers showed various degree of decrease in T% at different wavelengths. 42,56 With the decease of the retention times, the polymers could not be fully doped (oxidized) or dedoped (reduced), resulting in the decrease in the contrast ratios (T%). 57 On another aspect, these data suggested that PDTCZ-1 and PDTCZ-2 were hardly the best materials to be display-type devices, but might be the potential candidates in the applications of smart windows and other devices.…”
Section: Electrochromic Switchingmentioning
confidence: 99%
“…L* symbolizes the luminance of color from black to white, a* symbolizes the contrast of red versus green, and b* symbolizes the contrast of yellow versus blue. 25,56 Three thin lms of each polymer with different thickness participated in the experiments, and the thickness was described by the maximum optical absorption value, that is, the larger the value was, the thicker the lm was. Fig.…”
Section: Colorimetrymentioning
confidence: 99%